2017
DOI: 10.1007/s00737-017-0735-8
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and commitment therapy for perinatal mood and anxiety disorders: development of an inpatient group intervention

Abstract: Perinatal mood and anxiety disorders are a leading cause of morbidity and mortality for childbearing women. Current treatments, such as cognitive behavioral therapy and interpersonal therapy, have demonstrated modest success in addressing perinatal psychiatric symptoms; however, additional treatment options are needed to address the limitations of current approaches, particularly for women experiencing moderate to severe perinatal mental illness during pregnancy or postpartum. We discuss the use of acceptance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…Findings from previous studies indicate that psychological flexibility is indeed amenable to intervention and acceptance and mindfulness strategies to affect such change are readily available. To date, one group treatment based on ACT has been developed for perinatal mood and anxiety disorders but has yet to be fully evaluated [40]. Interestingly, results indicated that treatment conditions were differentially related to psychological flexibility early in the post NICU discharge period.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from previous studies indicate that psychological flexibility is indeed amenable to intervention and acceptance and mindfulness strategies to affect such change are readily available. To date, one group treatment based on ACT has been developed for perinatal mood and anxiety disorders but has yet to be fully evaluated [40]. Interestingly, results indicated that treatment conditions were differentially related to psychological flexibility early in the post NICU discharge period.…”
Section: Discussionmentioning
confidence: 99%
“…Distraction has been shown to be an effective regulation strategy for decreasing mothers' emotional intensity and bilateral amygdala activation while listening to infant cry sounds (Firk et al, 2018). Acceptance and commitment therapy (ACT) approaches, such as mindfulness and cognitive defusion may be particularly helpful among postpartum samples (Bonacquisti et al, 2017). Teaching mothers mindfulness skills can promote adaptive coping in stressful contexts (e.g., poverty, relationship conflict) and parenting challenges (e.g., nursing, sleep deprivation) to facilitate sensitive and responsive parenting (Duncan & Bardacke, 2010;Gershy et al, 2017).…”
Section: Study Limitations and Future Directionsmentioning
confidence: 99%
“…Recently, Acceptance and Commitment Therapy (ACT) has been highlighted as a psychological intervention that is well placed to meet the needs of women presenting with moderate‐to‐severe perinatal mood and/or anxiety disorders (Bonacquisti, Cohen, & Schiller, 2017). Commonly referred to as a ‘third wave’ or ‘contextual’ behavioural therapy, ACT is grounded in an empirical, principle‐focused approach (Hayes, Luoma, Bond, Masuda, & Lillis, 2006; Hayes, Villatte, Levin, & Hildebrandt, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of randomized controlled trials (RCTs) summarized in a series of systematic reviews and meta‐analyses attest to the efficacy of ACT for a range of psychiatric disorders and chronic health conditions including mood and anxiety disorders, psychosis, chronic pain, cancer, diabetes, epilepsy, obesity, and substance abuse (A‐Tjak et al ., 2015; Hayes et al ., 2011; Öst, 2014; Powers, Vording, & Emmelkamp, 2009; Ruiz, 2012). The trans‐diagnostic nature of ACT and the comorbidity of physical and mental health problems during the perinatal period are cited as reasons why ACT maybe uniquely beneficial for moderate‐to‐severe perinatal mental health problems (Bonacquisti et al ., 2017). However, to our knowledge, there are no published studies evaluating the feasibility, safety, or effectiveness of ACT for women with mood and/or anxiety disorders during the perinatal period.…”
Section: Introductionmentioning
confidence: 99%